Origins and the Enlightenment : aesthetic epistemology from Descartes to Kant - Labio, Catherine (Cornell University Press, 2004)
"The best way to understand the Enlightenment's obsession with origins is to study it in conjunction with the contemporary conceptualization of originality as a criterion of aesthetic value, Catherine Labio maintains. Her expansive survey of the era's thought places special emphasis on epistemology and is genuinely interdisciplinary, drawing on such fields as anthropology, geometry, historiography, literary criticism, and political economy."